Malaria transmission: current challenges and new tools in the elimination context – revisiting a workshop at IHMT - Isabel Craveiro; Gonçalves, Luzia; Varanda, Jorge; salgueiro, P. (Anais do Instituto de Higiene e Medicina Tropical, 2018)
Lately, regardless of considerable progress in the elimination of ma-laria, this disease remains a major public health problem in tropical regions, prevailing in countries with weak health systems. Increased investment in recent decades resulted in the development of new tools and solutions for the control of the parasitic disease with the greatest impact on humanity.The Centre for Global Health and Tropical Medicine hosted a scienti-fic meeting on current challenges and innovative tools in the context of malaria elimination. From the beginning, the organizing commit-tee, with a multidisciplinary composition, had as main purposes to discuss the current approaches to study the malaria transmission and to identify new tools to measure the transmission in different malaria contexts, including pre-elimination scenarios. In this paper we present a synthesis of the two days of the workshop, of its participants and main contents. In addition, we sought to reflect on the multidiscipli-nary nature of presentations and discussions, and the importance of working together to achieve the goal of eliminating malaria